Predictors of Nutritional Risk in Community-dwelling Seniors - Roberts, Karen C. (Can J Public Health, 2007)
OBJECTIVES: At any age, good nutrition is important for maintaining good health. Seniors are at risk of declining nutritional status due to the physiological, psychological, economic and social changes that accompany aging. We investigated medical, psychological, social and environmental characteristics as both correlates and predictors of elevated nutritional risk in community-dwelling seniors. METHODS: Data came from a prospective study of 839 seniors aged 75 and over, in Montreal. Face-to-face interviews were conducted at baseline and at 12 months. The validated Elderly Nutrition Screening (ENS©) tool was administered and subjects were assigned a level of “nutritional risk” based on the risk for energy and nutritional intake deficiencies. Using risk factors identified in the literature, analyses were performed to characterize those factors associated with both the level of risk at baseline and a change in risk over 12 months. RESULTS: At baseline, more than half (60%) of the participants were at elevated nutritional risk. Cross-sectional analyses supported the findings of previous research examining correlates of elevated nutritional risk. Longitudinal results showed that among those at low nutritional risk, only poor self-rated health was found to be a statistically significant predictor of elevated risk at 12 months (OR=3.30, p<0.05). CONCLUSION: Proper nutrition can promote healthy aging by preventing disease and disability, improving health outcomes and maintaining autonomy, resulting in decreased health care utilization and costs. The findings of this research highlight the need for longitudinal studies in order to better understand and target nutritional risk in community-dwelling seniors.